DETERMINANTS OF ADOPTION OF IMPROVED RICE VARIETIES: EFFECTS ON OUTPUT IN VOLTA REGION - Mabe, F. N.; Ehiakpor, D. S.; Adam, B.; Dumasi, D. E. (UDS International Journal of Development, 2019)
Adoption of improved rice varieties has become very important in Ghana especially in major producing regions like Volta. This is because rice yield is generally low in the country. This study investigated and analyzed the determinants of adoption of improved rice varieties. The study also analyzed the effects of adoption of improved rice varieties on rice output. Primary data was collected through semi-structured questionnaires from 177 farmers. The districts, communities and farmers were selected using simple random sampling technique. Analysis of data was carried out using the Heckman Sample Selection Model. From the results, 54% of the respondents used improved rice varieties while 46% did not. The results also show that age, the frequency of extension visits, farmers’ experience, access to irrigation, business as a purpose of farming and access to credit are the main drivers of adoption of improved seeds. Again, factors that influence rice output are extension officers’ visit to the farm, education, farming experience and access to irrigation facility. Adoption of improved rice varieties increases rice output. It is therefore recommended that farmers should be educated to adopt improved rice varieties. Institutions that are in charge of dissemination of improved rice seeds should target young farmers who have access to extension services, irrigation and are cultivating rice purposely for business. Keywords: Adoption, improved rice varieties, Heckman Sample Selection Model